After the fall (how Humpty Dumpty got back up again) - Santat, Dan 1975- (Roaring Brook Press, 2017)
After falling off the wall, Humpty Dumpty is very afraid of climbing up again, but is determined not to let fear stop him from being close to the birds
Keywords: Characters in literature; Determination (Personality trait); Fear; Bilderbuch